The perceptual effect of forms used on walls and furnishings in cafés - Yildirim, Kemal; Muezzinoglu, Mensure Kubra (Emerald Group Publishing Ltd, 2024)
Purpose- This study researched the effects on the perceptual evaluations of participants for the physical environmental factors of caf & eacute;s using curvilinear, rectilinear, and mixed forms to provide for the spatial states of belonging, to increase the pleasures, and to extend the periods of remaining in the space. Design/methodology/approachThis study used virtual reality (VR) technology to model the caf & eacute;s designed by using curvilinear, rectilinear and mixed forms as an experimental environment. After experiencing the virtual images of the experimental spaces, participants filled out a spatial perception questionnaire. Perceptual evaluations of 415 participants regarding the environmental factors of caf & eacute;s designed using curvilinear, linear and mixed forms were analyzed in a computer environment. Findings- According to the analysis of the questionnaire data, the caf & eacute;s using mixed forms were perceived as more positive for the factors of appeal (inviting, restful, warm and sincere), planning (well-planned) and space freedom (roomy, uncluttered, uncrowded, large, wide and free space) compared with the caf & eacute;s using curvilinear and rectilinear forms. Furthermore, the caf & eacute;s using curvilinear forms were perceived as more positive for all elements compared with the caf & eacute;s using rectilinear forms. However, there was a more negative approach in the perceptual evaluations of participants connected to increases in level of education. Originality/value- The research results clearly demonstrated that the different interior and furniture forms frequently encountered in caf & eacute;s cause significant effects on users' perceptual evaluations.
Keywords: Caf & eacute; interior; Wall; Furnishing; Curvilinear form; Rectilinear form; Mixed form